Hydraulic fracturing experiments in tight formations - Rasouli, Vamegh (APCBM, 2011)
Hydraulic fracturing is perhaps the major stimulation technique which is used to enhance production in low permeability reservoirs and also in unconventional resources such as tight formations, shale gas and Coalbed Methane. Performing lab simulations, before real field practices, to understand different aspects of complicated process involved in a fracturing job would be very beneficial. For this purpose, and in order to consider the effect of all three principal stresses in the field the experiments must be conducted on a cube shaped sample. Using the true tri-axial stress cell (TTSC) developed at the Department of Petroleum Engineering of Curtin University it is possible to simulate a fracturing job on samples up to 30cm. Three independent stresses can be applied to the sample with pore pressure being increased independently. The fluid injection causes the fracture to develop within the sample. We have performed lab experiments on very small size cube samples of 5 cm. No similar experiments have been reported in the literature which is believed to be due to the need for expensive laboratory set up and accurate measurement facilities. This is while the maximum sample size that can be retrieved from downhole is no more than 5 cm: this indicates the importance of lab experiments on this sample size. The initial experiments carried out on synthetically made samples and on a few real tight sandstones indicated very successful results which supports the idea of testing small scale samples. Performing hydraulic fracturing in the lab on small size samples with the objective of upsclaing the results to represent real field practices needs applying the scaling laws.Different scaling laws proposed in the past have been used in this study to investigate their applications on tight formations. It was possible to conduct this study on synthetically made samples with different sizes and assess the applicability of the scaling laws. The preliminary results are in a relatively good agreement with numerical simulations which were performed for calibration purposes. The results of some of the lab experiments performed using the TTSC will be presented in this paper and conclusions will be made.